2014
DOI: 10.1590/0103-6440201300054
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Glucose Transporters 1 and 3 in Metastatic and Non-Metastatic Lower Lip Squamous Cell Carcinoma

Abstract: This study aimed to evaluate the immunoexpression of glucose transporters 1 (GLUT-1) and 3 (GLUT-3) in metastatic and non-metastatic lower lip squamous cell carcinoma (LLSCC). Twenty LLSCCs with regional nodal metastasis and 20 LLSCCs without metastasis were selected. The distribution of staining and the percentage of GLUT-1 and GLUT-3 staining in each tumor core and at the deep invasive front were assessed. Most tumors (70%) exhibited peripheral staining for GLUT-1 in nests, sheets and islands of neoplastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
4
6
0
1
Order By: Relevance
“…This pattern of peripheral staining of GLUT-1 was also observed by others. 14,15,21,22 High percentage of GLUT-1 expression was associated with poorly differentiated SCC, agreeing with Mendez et al 23 Regarding BCC, to our knowledge, we are the first study to demonstrate the expression of GLUT-1 in this common cutaneous malignancy. The current study demonstrated its expression in 62.5% of BCCs, and the expression was seen mainly in the central portion of the malignant basaloid nests, which may be related to focal keratinization in BCC as an indicator of follicular differentiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This pattern of peripheral staining of GLUT-1 was also observed by others. 14,15,21,22 High percentage of GLUT-1 expression was associated with poorly differentiated SCC, agreeing with Mendez et al 23 Regarding BCC, to our knowledge, we are the first study to demonstrate the expression of GLUT-1 in this common cutaneous malignancy. The current study demonstrated its expression in 62.5% of BCCs, and the expression was seen mainly in the central portion of the malignant basaloid nests, which may be related to focal keratinization in BCC as an indicator of follicular differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…This pattern of peripheral staining of GLUT-1 was also observed by others. 14,15,21,22 High percentage of GLUT-1 expression was associated with poorly differentiated SCC, agreeing with Mendez et al 23 in cervical SCC and Pinheiro et al 24 in breast carcinoma. The association with high-grade tumors explained the peripheral localization of GLUT-1 in the less-differentiated cells in the periphery of malignant nests of SCC.…”
Section: Discussionsupporting
confidence: 79%
“…OKs and AMs showed staining in the membrane on 55% of samples; these differences were statistically significant. The results obtained for DC lesions were similar to Demeda et al that verified staining occurred most frequently in the membrane/cytoplasm in the invasion front of squamous cell carcinoma of the lower lip. The study by Salla et al showed similar results with regard to the staining in OK and AM lesions, where the membrane was most commonly stained in samples of peripheral nerve sheath benign oral lesions.…”
Section: Discussionsupporting
confidence: 87%
“…Overexpression of GLUT‐1 has been found in a series of cancer lesions such as breast, lung, liver, stomach, ovary, bladder, head and neck and oral cancers and has been used as a diagnostic and prognostic tool . In the present study, the expression of GLUT‐1 was observed in all three lesions studied.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation